Breast Reconstruction Outcomes after Nipple-Sparing Mastectomy and Radiation Therapy. Issue 4 (April 2015) - Reish, Richard G.; Lin, Alex; Phillips, Nicole A.; Winograd, Jonathan; Liao, Eric C.; Cetrulo, Curtis L.; Smith, Barbara L.; Austen, William G.; Colwell, Amy S.
Abstract : Background: Few studies in the literature examine outcomes of immediate breast reconstruction after mastectomy with nipple preservation and radiation therapy. Methods: Retrospective analysis of multisurgeon consecutive implant-based reconstructions after nipple-sparing mastectomy from June of 2007 to December of 2012 was conducted at a single institution. Results: Six hundred five immediate breast reconstructions were performed following nipple-sparing mastectomy, of which 88 were treated with radiation therapy. There was a trend toward more complications in patients with radiation (19.3 percent versus 12.8 percent; p = 0.099) associated with a higher rate of implant loss (6.8 percent versus 1.0 percent; p = 0.001). Preoperative radiotherapy had a higher risk of total complications ( p = 0.04; OR, 2.225; 95 percent CI, 1.040 to 4.758) and postoperative radiotherapy had a higher risk of explantation ( p = 0.015; OR, 5.634; 95 percent CI, 1.405 to 22.603). There were no significant differences in nipple removal secondary to malposition or positive oncologic margins in patients with radiation compared to those without radiation. Patients with radiation did have a higher incidence of secondary procedures for capsular contracture (12.5 percent versus 2.3 percent; p < 0.001) and fat grafting (13.6 percent versus 3.9 percent; p < 0.001). The total nipple retention rate in patients with radiation therapy was 90 percent (79 of 88), and the reconstruction failure rate was 8 percent. Conclusions: Nipple-sparing mastectomy and immediate reconstruction in patients who had or will receive radiation therapy is associated with a higher incidence of complications and operative revisions compared with patients without radiation. However, most patients have successful reconstructions with nipple retention and no recurrences. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.